Advances in the knowledge of the antiviral immune response and resistance to Viral Haemorrhagic Septicaemia Virus (VHSV) in turbot (Scophthalmus maximus) - Pereiro González, Patricia
Although turbot aquaculture is well established, several pathogens can affect its health status, causing important economic losses. VHSV is one of the main threats in turbot farms due to the absence of treatments and vaccines for VHSV. The first goal of this thesis was to increase the information available in public databases regarding the transcriptome sequences associated with the antiviral immune response of turbot. A microarray highly enriched in antiviral sequences was constructed using this information. This allowed us to conduct a broad transcriptome analysis of the response to VHSV infection and evaluate the activity of a DNA vaccine against VHSV. This information led us to focus our attention on certain molecules or processes affected by the vaccine/infection. This was the case for two type I interferons (IFNs), which were characterized and studied for the first time in turbot. In order to complete our knowledge about the IFNs, we also sought to investigate the role of the type II IFN (IFN-gamma).